Three new species of Labeninae (Hymenoptera: Ichneumonidae) from Costa Rica - Zuñiga, Ronald; Hanson, Paul (Zootaxa, 2025)
As a result of continuing research on the ichneumonids of Costa Rica three new species of Labeninae are described: Apechoneura fuentesi Zuñiga & Hanson, Grotea acunae Zuñiga & Hanson, and Labena murilloi Zuñiga & Hanson. To aid in the identification of these new species illustrations and modifications to existing keys are provided. With the description of these new species, there are now 47 species known from the country. Updated summaries are provided of the biology of each genus.